Implikasi Sikap Memaafkan Terhadap Kualitas Manusia: Studi Tafsir Al-Alusi terhadap Mahasiswa dan Masyarakat Muslim di Kota Medan - Pimpinan Abaik Simamora; Syahrin Harahap (Jurnal test, 2025)
This study aims to examine in depth the concept of forgiveness (al-‘afw) in the perspective of al-Ālūsī’s interpretation of Rūḥ al-Maʿānī, focusing on relevant verses of the Qur’an and field studies of students and Muslim communities in Medan; QS al-Baqarah: 109, QS al-A‘rāf: 199, QS ash-Syūrā: 40, QS an-Nūr: 22, and QS al-Furqān: 63. This study uses a qualitative method with a case study approach to the interpretation of Al-Alusi as a grand theory used with a thematic (maudu’i) - Sufi approach. The main data were obtained through an in-depth study of the text of the interpretation of al-Ālūsī which was analyzed conceptually and thematically. The results of the study show that forgiveness in al-Ālūsī's interpretation has three main layers of meaning: first, as noble self-control and a manifestation of noble morals; second, as an expression of spiritual power that can only be carried out by spiritually empowered individuals; and third, as the pinnacle of prophetic ethics and the basic principle of prophetic civilization. In contemporary ethics, the value of forgiveness as explained by al-Ālūsī is relevant as a universal ethical foundation that emphasizes moderation, emotional control, and respect for human dignity. The conclusion is that al-Ālūsī's interpretation provides a strong conceptual framework for understanding forgiveness as a transcendent spiritual and ethical value. Forgiveness is an indicator of superior human qualities that are able to go beyond revenge to strengthening morals and spirituality in socio-religious life.